Non-ideal compressible fluid dynamics for propulsion and power : selected contributions from the 2nd International Seminar on Non-Ideal Compressible Fluid Dynamics for Propulsion & Power, NICFD 2018, October 4-5, 2018, Bochum, Germany /: selected contributions from the 2nd International Seminar on Non-Ideal Compressible Fluid Dynamics for Propulsion & Power, NICFD 2018, October 4-5, 2018, Bochum, Germany. (2020) - Unknown
No abstract available